2022
DOI: 10.21715/gb2358-2812.202236005
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruptors, estrogenic activity by the YES bioassay, and acute toxicity in Southeastern Brazil metropolitan surface waters

Abstract: This study aimed to determine endocrine disruptors in urbanized rivers Maracanã and Mangue Channel in Rio de Janeiro the second most populated city in Brazil. Bisphenol A, 17β-estradiol, estriol, and 17α-ethinylestradiol were determined by high-performance liquid chromatography with a diode array detector and fluorescence detector In addition, the evaluation of estrogenic activity was performed by the YES bioassay (Yeast estrogen screen) with the Saccharomyces cerevisiae yeast, and acute toxicity assays were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The estrogenic activity via yeast screening assay of each water sample measured as 17β-estradiol relative estrogenicity is summarized in Table 2 . The relative estrogenic activities of all samples were comparable to those of other yeast assays [ 28 , 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The estrogenic activity via yeast screening assay of each water sample measured as 17β-estradiol relative estrogenicity is summarized in Table 2 . The relative estrogenic activities of all samples were comparable to those of other yeast assays [ 28 , 46 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 67%
“…The data show that open-source water has estrogenic activity of 2.5–9.5 ng/L and is not far from most countries in the world, including bordered countries [ 28 , 46 , 47 , 48 ]. It has been reported that the estrogenic activity of surface water typically should be below 25 ng/L, including the effluent of the water treatment plant [ 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%